Learning trajectory of quadrilaterals learning using the context of Burongko Bugis cake to improve students’ critical thinking - Andi Aras; Fawziah Zahrawati; Zulfiqar Busrah; Claver Nzobonimpa (Jurnal Elemen, 2022)
One goal of learning mathematics is to foster students’ critical thinking skills, but this has not been realized well in Indonesia. This study aims to produce a learning trajectory that can help students grow their critical thinking skills in studying quadrilaterals using the Burongko cake context. This study uses a design research method that comprises three stages, namely (1) preliminary design, (2) experimental design, and (3) retrospective analysis. This research was conducted at Madrasah Tsanawiyah As’adiyyah Bontouse with 25 students, nine males and 16 females of class VIII B. The results showed that this learning trajectory could improve students’ understanding of learning quadrilaterals with ease and fun because mathematical concepts are associated with students’ daily habits. The resulting learning trajectory is relevant to indicators of critical thinking skills, including interpretation, analysis, evaluation, and decision making. It was found that there was no significant difference in critical thinking skills between students who had high mathematical abilities and low mathematical abilities. Subjects with high mathematical abilities could carry out critical thinking processes to solve problems much better than subjects with low mathematical abilities. The results provide information about the use of local Bugis culture as a context of learning mathematics to improve students’ critical thinking.